An Am Stereo System with Additional Data Transmission - Istvan Standeisky (Communications - Scientific letters of the University of Zilina, 1999)
Previously proposed systems for AM stereo are discussed. The new compatible AM stereo system is described. The new system makes it possible to implement a stereo transmission with a bandwidth in the sound channels from 50 Hz to 4.5 (or more) kHz and a data transmission with a modulation rate of 25 bit/sec.